1968
DOI: 10.1080/00049536808255754
|View full text |Cite
|
Sign up to set email alerts
|

The reliability of behavioural measures obtained in the open-field

Abstract: Seven open-field measures (defecation, urination, ambulation, washing, rearing, latency, and inner circle activity) were obtained using a number of different scoring methods for albino and hooded rats.The albino Ss were tested on 3 different occasions. The first test session was conducted when Ss were 90 days old, the second test session was held 63 days later and a third test session was conducted 154 days after the second. The hooded rats were subjected to 1 test session when Ss were 90 days old. The reliabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0

Year Published

1976
1976
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(26 citation statements)
references
References 7 publications
2
24
0
Order By: Relevance
“…Table 1 (as well as the defecation-related correlations in Table 2) seem to be consistent with the above analysis, and indeed suggest that the defecation measure is a reliable one. Our observation of a significant positive correlation (.81) between open-field ambulation and rearing is in agreement with the results of a number of previous studies (e.g., Ivinskis, 1968;Ray & Hockhauser, 1969). In the present study, open-field defecation was observed to have a significant negative correlation with ambulation (-.59) and with rearing (-.49), a finding which supports a number of previous studies in which negative correlations were found between defecation and the open-field activity variables (e.g., Hall, 1936;Holland & Gupta, 1966;Tachibana, 1982;Whimbey & Denenberg, 1967).…”
Section: Resultssupporting
confidence: 83%
See 2 more Smart Citations
“…Table 1 (as well as the defecation-related correlations in Table 2) seem to be consistent with the above analysis, and indeed suggest that the defecation measure is a reliable one. Our observation of a significant positive correlation (.81) between open-field ambulation and rearing is in agreement with the results of a number of previous studies (e.g., Ivinskis, 1968;Ray & Hockhauser, 1969). In the present study, open-field defecation was observed to have a significant negative correlation with ambulation (-.59) and with rearing (-.49), a finding which supports a number of previous studies in which negative correlations were found between defecation and the open-field activity variables (e.g., Hall, 1936;Holland & Gupta, 1966;Tachibana, 1982;Whimbey & Denenberg, 1967).…”
Section: Resultssupporting
confidence: 83%
“…Correlations between ambulation and defecation scores have been studied most often, and there seems to be generalagreement that a negative correlation existsbetween these two measures, although some studies have failed to find significant correlations (see Archer, 1973, Table V, for a review of the rat literature). Correlations between ambulation and rearing, not surprisingly, have usuallyresulted in significantpositivecorrelations (e.g., Anderson, 1938;Ivinskis, 1968;Pare, 1964;Ray & Hockhauser, 1969), even though these two motor behaviors are mutually exclusive. When rearing and defecation measures have been correlated, negative correlations have usually been found, but these are of smaller magnitude than those between ambulation and defecation (e.g., Holland & Gupta, 1966;Tachibana, 1982).…”
Section: The Open-field Testmentioning
confidence: 99%
See 1 more Smart Citation
“…A high frequency or duration of these behaviors indicates high exploratory behavior and low anxiety levels. However, the number of grid lines crossed and frequency of rearing and grooming were adopted as indices of anxiety/fear in the present study and have been documented as reliable and valid measures of emotional behavior (Ivinskis, 1968;Prescott, 1970). Table 1 shows that orchiectomized animals exhibited a significant reduction of exploratory behavior, indicating elevated fear or increased anxiety, and this observation was consistent with previous open field studies (Hall, 1934;Archer, 1973;Blanchard, Griebel,& Blanchard, 2001).…”
Section: Discussionsupporting
confidence: 79%
“…Ivinskis (1966Ivinskis ( , 1968 and others (e.g., Price & Huck, 1976;Ray & Hockhauser, 1969) found positive correlations of a magnitude similar to those reported between movement into squares and rears (even though those behaviors are mutually exclusive) and considered rearing and ambulation to be measures of a single behavioral dimension.…”
Section: Discussionmentioning
confidence: 92%